2017
DOI: 10.1002/mop.30566
|View full text |Cite
|
Sign up to set email alerts
|

A single layer negative index meta atom at microwave frequencies

Abstract: A single layer negative index meta atom is described that is developed by an outer and inner split ring resonators with inverse E‐shape metal strips of copper are connected with the outer ring resonator that look like a mirror‐shape structure. Finite integration technique based CST Microwave Studio is utilized to design, simulation and analysis purposes, where the Agilent N5227A vector network analyzer is used for measurement. Measurements shows that, the measured and simulated performances are well complied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Also, a split ring resonator (SRR) meta-atom structure and tree-shaped fractal FSS for C-, X-, and Ku-band applications are presented in. 22,23 Nonetheless, the stability of proposed surfaces at oblique angles of incidence is not discussed. Additionally, double negative metamaterial exhibiting negative refractive index bandwidth of 3.6 GHz having potential for wideband EM shielding is discussed in.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a split ring resonator (SRR) meta-atom structure and tree-shaped fractal FSS for C-, X-, and Ku-band applications are presented in. 22,23 Nonetheless, the stability of proposed surfaces at oblique angles of incidence is not discussed. Additionally, double negative metamaterial exhibiting negative refractive index bandwidth of 3.6 GHz having potential for wideband EM shielding is discussed in.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the frequency response of the proposed absorber degrades with a change in the incident angle of the striking wave. Also, a split ring resonator (SRR) meta‐atom structure and tree‐shaped fractal FSS for C‐, X‐, and Ku‐band applications are presented in 22,23 . Nonetheless, the stability of proposed surfaces at oblique angles of incidence is not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a MTM design that enhanced nonlinear response with strong artificial magnetism, ensures a negative refractive index with bistable and self‐tunable response at 2011 . A single layer negative index meta‐atom was developed for tri‐band applications printed on Rogers RT 5880 material . An omega‐type MTM operating in X and Ku‐bands for a continuous negative‐zero‐positive index dispersion was discussed in Zhang et al LHET lenses work in the cut‐off region of the circular waveguide formed by consecutive stacked holes, which leads to a negative index of refraction, presented in Cía et al A graded photonic crystal consisted of dielectric rods with spatially varying radii was used to control electromagnetic field pattern by Aghanejad et al in 2012 .…”
Section: Introductionmentioning
confidence: 99%
“…12 A single layer negative index meta-atom was developed for tri-band applications printed on Rogers RT 5880 material. 13 An omega-type MTM operating in X and Ku-bands for a continuous negative-zero-positive index dispersion was discussed in Zhang et al 14 LHET lenses work in the cut-off region of the circular waveguide formed by consecutive stacked holes, which leads to a negative index of refraction, presented in Cía et al 15 A graded photonic crystal consisted of dielectric rods with spatially varying radii was used to control electromagnetic field pattern by Aghanejad et al in 2012. 16 A 130 × 190 mm 2 Luneburg lens antenna based on parallel-plate waveguide was used to operate in X-band (from 8.0 to 12.0 GHz), and the focusing condition of the lens for gradient index was achieved by the use of complementary non-resonant MTM structures in Dhouibi et al 17 An octave-bandwidth highly directive half Maxwell fish-eye lens antenna was shown in C-band (from 3.0 to 7.5 GHz), which was implemented by gradient-refractive-index MTMs.…”
Section: Introductionmentioning
confidence: 99%